พฤติกรรมในการบริโภคน้ำดื่มบรรจุขวดของครัวเรือน ในเขตอำเภอฝาง จังหวัดเชียงใหม่ - ธัญรัศม์ สิทธิสวน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
This study on “Bottled Drinking Water Consumption Among Households in Fang District, Chiang Mai Province” had the objectives of 1) investigating the bottled drinking water consumption among the households in Fang District and 2) examining the factors influencing the bottled drinking water consumption among the households in the district. Data was collected using 400 questionnaires of which 100% were filled out and returned. The Statistical Package for Social Science program was used for data analysis along with the statistical methods of frequency, percentage, mean, standard deviation and t-test as well as F-test together with Pearson’s Produce Moment Correlative Coefficient. The results could be summed up as follows: 1. As for personal data, most of the respondents were male, 350 in number or 47.5%. Most of them conducted a private business, 174 cases or 43.5% and 179 had a secondary education (44.70%). The household income per month was around 5,001-10,000 Baht, 171 respondents or 42.70% with 4-6 members per household (55.70%). 2. Regarding their consumption of bottled water, most of them used the home delivery service of the producers as it was convenient and the period of consumption was over two years. The reasons for drinking the bottled water were mostly due to confidence in its being clean, quality and safety. The majority of the clients were familiar with the brands from their previous purchase and drinking. Others were directly introduced by the producer or company coming to their houses or a producer was one of their acquaintances and some were recommended by their neighbors. The amount they spent on bottled drinking water was 50-100 Baht monthly. Most of the respondents felt that the price was reasonable and they never had problems with consumption. 3. The market mix factors for consuming bottled drinking water was at an overall moderate level. The aspect of the production factors of bottled drinking water was a concern at a high level, the factors about cost at a moderate level, its distribution at a high level and its market promotion was at a moderate level. 4. Results of testing the hypothesis revealed that for the first hypothesis on the basic factors of the household members: sex, age, profession, education, income and the number of family members, these did not affect their consumption of bottled drinking water. So, the first hypothesis was dropped. The test of the second hypothesis: the overall market mix factors showed a very high level of relationship to the consumption at r=.841 with a statistical significance of 0.01, so the second hypothesis was accepted.